KEBIJAKAN PEMERINTAH DI MASA PANDEMI COVID-19 TERHADAP KEMASLAHATAN PERKEMBANGAN UMKM BANDA ACEH - Cut Dian Fitri; Rina Desiana; Siti Laila Rahmatina (Al-Ijtima`i: International Journal of Government and Social Science, 2022)
Government Policy in the Covid-19 Pandemic Period Agains the Benefits of MSME Development in Ie Masen Kayee Adang Village Banda Aceh enforced a system with theEnforcement of Community Activity Restrictions so as to reduce activities outside the home. This study aims to determine the impact of the Covid-19 pandemic on the development of MSMEs in Ie Masen Kayee Adang Village and government policies during the Covid-19 period for the benefit of MSME development in Ie Masen Kaye Adang Village. This study uses a qualitative descriptive approach by collecting data using the method of observation, documentation, and interview methods. The results of this study indicate that a number of parties related to the presence of the COVID-19 pandemic have had a major impact due to the policy of school and office holidays as well as social distancing. There has been a decline in the income of MSME actors by more than 50%.